A powdered Ni / La / SBA-15 catalyst and its preparation method and use

By using powder Ni/La/SBA-15 catalyst, the yield and stability problems of existing catalysts in sorbitol hydrogenolysis reaction were solved, and the efficiency of low-carbon alcohols was achieved, and the activity and stability of the catalyst were significantly improved.

CN115888796BActive Publication Date: 2025-03-18NINGBO HUANYANG CHEM

Patent Information

Application Number
CN202211479822.3
Authority / Receiving Office
CN · China
Patent Type
Patents(China)
Current Assignee / Owner
Filing Date
2022-11-24
Publication Date
2025-03-18
Estimated Expiration
2042-11-24

AI Technical Summary

Technical Problem

The existing catalysts have yield and stability problems in the sorbitol hydrogenolysis reaction. The copper catalyst is prone to deactivate, the ruthenium catalyst has low activity and high cost, the sorbitol content in the metal frame catalyst reaction raw materials is low, and the yield of low-carbon alcohols obtained from hydrogenolysis is also low.

Method used

The powder Ni/La/SBA-15 catalyst is used, which consists of nickel oxide, lanthanum oxide and SBA-15 molecular sieve. Through specific preparation methods and process conditions, the specific surface area of ​​the catalyst and the dispersion of nickel are improved, and its activity and stability are enhanced.

Benefits of technology

The high-efficiency preparation of low-carbon alcohols such as 1,2-propanediol and ethylene glycol in the sorbitol hydrogenolysis reaction was achieved. The catalyst still maintains high activity after 500 hours of operation, and has good anti-carbon deposit performance and stability.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure BDA0003960973050000101
    Figure BDA0003960973050000101
  • Figure HDA0003960973060000011
    Figure HDA0003960973060000011
  • Figure HDA0003960973060000012
    Figure HDA0003960973060000012
Patent Text Reader

Abstract

The present invention relates to a powdered Ni / La / SBA-15 catalyst, a preparation method thereof and its use. The powdered Ni / La / SBA-15 catalyst is composed of nickel oxide, lanthanum oxide and SBA-15 molecular sieve; wherein the content of nickel element is 10.0-25.0% by weight of the catalyst, the content of lanthanum element is 3.0-10.0% by weight of the catalyst, and the remainder is the total content of oxygen element and SBA-15 molecular sieve. The powdered Ni / La / SBA-15 catalyst of the present invention is applied to a method for preparing low-carbon alcohols by hydrogenation of sorbitol, showing good catalytic activity, sorbitol conversion rate greater than 96%, low-carbon alcohol total yield greater than 75%, and the catalyst is operated in a fixed bed reactor for 500h without significant decrease in activity and selectivity, and has good industrial application prospects.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention belongs to the technical field of catalysts. More specifically, the present invention relates to a powdered Ni / La / SBA-15 catalyst, a preparation method of the catalyst, and a use of the catalyst. Background Art

[0002] Biomass conversion is a very promising and huge topic, and has always been a research hotspot for scholars in various countries. Among them, the preparation of low-carbon alcohols such as 1,2-propylene glycol and ethylene glycol, which have huge market demand, by hydrogenolysis of low-cost and readily available glucose is undoubtedly a very attractive topic.

[0003] In the traditional production method, propylene oxide is used as the raw material to produce 1,2-propylene glycol, ethylene oxide is used as the raw material to produce ethylene glycol, and butylene oxide is used as the raw material to produce 1,2-butanediol. These all require petroleum as the basic raw material, and with the increasing difficulty of oil extraction, the price of oil will inevitably be higher, so the preparation of low-carbon alcohols from cheap biomass will have economic advantages. In the reaction process of preparing low-carbon alcohols from glucose, sorbitol must be obtained first, and the yield and stability of the catalyst for the hydrogenolysis of sorbitol to prepare low-carbon alcohols have always been a difficult problem to be solved, so in-depth research on sorbitol hydrogenolysis catalysts is a very meaningful topic.

[0004] CN 102731259A discloses the use of a Cu-based supported catalyst in the hydrogenolysis of sorbitol. The patent application discloses that sorbitol can be completely converted under the conditions of not more than 200°C and 6MPa, and the yields of 1,2-propylene glycol and ethylene glycol are higher than 50%. However, the patent application does not disclose the life experiment of the catalyst stability, and the copper catalyst is also very easy to deactivate in a reaction system with a large water content.

[0005] CN 101850249B discloses the use of a regular structure ruthenium catalyst in the hydrogenolysis of sorbitol. The catalyst exhibits high selectivity for 1,2-propylene glycol and ethylene glycol, but the catalyst activity is not high and ruthenium is expensive, which easily causes great cost pressure.

[0006] CN 101199930A discloses a catalyst synthesized by melting at high temperature with a metal as a skeleton, which has certain stability in the sorbitol hydrogenolysis reaction. However, the sorbitol content in the reaction raw material is low, which is not conducive to expanding production, and the yield of low-carbon alcohol obtained by hydrogenolysis is also low.

[0007] In view of the defects of the prior art, the inventors have finally completed the present invention after summarizing the prior art and conducting a large number of experiments and studies. Summary of the invention

[0008] Technical issues to be solved

[0009] The purpose of the present invention is to provide a powdered Ni / La / SBA-15 catalyst.

[0010] Another object of the present invention is to provide a method for preparing the powdered Ni / La / SBA-15 catalyst.

[0011] Another object of the present invention is to provide use of the powdered Ni / La / SBA-15 catalyst.

[0012] Technical Solution

[0013] The present invention is achieved through the following technical solutions.

[0014] The invention relates to a powdered Ni / La / SBA-15 catalyst.

[0015] The catalyst is composed of nickel oxide, lanthanum oxide and SBA-15 molecular sieve; wherein the content of nickel element is 10.0-25.0% based on the total weight of the catalyst, the content of lanthanum element is 3.0-10.0% based on the total weight of the catalyst, and the balance is the total content of oxygen element and SBA-15 molecular sieve; the nickel oxide is a face-centered cubic crystal with a grain size of less than 10nm; the lanthanum oxide is a hexagonal crystal with a grain size of less than 15nm; the specific surface area of ​​the catalyst is 350m 2 / g or above.

[0016] The invention also relates to a method for preparing the powdered Ni / La / SBA-15 catalyst.

[0017] The preparation steps of the preparation method are as follows:

[0018] A. Preparation of mixed solution

[0019] 20.0-40.0 parts by weight of a soluble nickel salt, 2.0-10.0 parts by weight of a soluble lanthanum salt, 5.0-15.0 parts by weight of aqueous ammonia and 25.0-45.0 parts by weight of a fuel are stirred and mixed to obtain a mixed liquid;

[0020] B. Mixing and drying

[0021] According to the volume ratio of the mixed liquid to the carrier of 1:0.8-1.2, the mixed liquid obtained in step A is added to the SBA-15 molecular sieve carrier, stirred and mixed evenly, and then allowed to stand at room temperature for 1-4 hours to allow the mixed liquid to be fully impregnated into the carrier, and then dried in an oven at a temperature of 80-110° C. for 12-16 hours to obtain a solid powder with a water content of less than 2.0% by weight;

[0022] C. Combustion and roasting

[0023] The solid powder obtained in step B is ignited in a muffle furnace at a temperature of 300-350° C. for 0.5-1.0 h, then heated to 500-600° C. at a heating rate of 2-4° C. / min, and calcined at this temperature for 2-5 h to obtain the powdered Ni / La / SBA-15 catalyst.

[0024] According to a preferred embodiment of the present invention, in step A, the soluble nickel salt is nickel nitrate.

[0025] According to another preferred embodiment of the present invention, in step A, the soluble lanthanum salt is lanthanum nitrate.

[0026] According to another preferred embodiment of the present invention, in step A, the fuel is one or more organic fuels selected from glycine, ethylene glycol or citric acid.

[0027] According to another preferred embodiment of the present invention, in step A, the concentration of the aqueous ammonia is 25-28% by volume.

[0028] According to another preferred embodiment of the present invention, in step B, the crystal form of the SBA-15 molecular sieve is a hexagonal crystal form, and its specific surface area is 400 to 1000 m 2 / g, its total pore volume is 1.2-2.5 ml / g, its average pore diameter is 5-15 nm, and its particle size is 6250-12500 mesh.

[0029] The present invention also relates to the use of the powdered Ni / La / SBA-15 catalyst or the powdered Ni / La / SBA-15 catalyst prepared by the preparation method in preparing low-carbon alcohols by hydrogenating sorbitol.

[0030] According to a preferred embodiment of the present invention, the preparation steps of preparing low-carbon alcohols by hydrogenation of sorbitol are as follows:

[0031] I. Forming and filling

[0032] Using a tablet press, the powdered Ni / La / SBA-15 catalyst and powdered calcium hydroxide are respectively pressed into catalyst sheets and calcium hydroxide sheets with a diameter of 3 to 6 mm and a thickness of 2 to 5 mm, and then the catalyst sheets and calcium hydroxide sheets are mixed and filled into a fixed bed reactor at a weight ratio of 1:0.5 to 1.5 to form a catalyst bed;

[0033] II. Catalyst Activation

[0034] Allowing reducing gas to pass through the catalyst bed at a flow rate of 150 to 450 catalyst bed volumes per hour, while heating the catalyst bed to a temperature of 450 to 550° C. at a heating rate of 1.0 to 4.0° C. per minute, and activating the Ni / La / SBA-15 catalyst at this temperature for 2 to 5 hours;

[0035] III. Hydrogenolysis

[0036] A mixed solution consisting of 10-50% sorbitol, 15-45% water and 30-60% methanol by weight is pumped into a fixed bed reactor through a pipeline. At the same time, high-pressure hydrogen is also transported into the fixed bed reactor through a pipeline. When the molar ratio of hydrogen to sorbitol is 10-30:1 and the feed volume space velocity is 0.5-2.5h -1 , reacting at a temperature of 190 to 240° C. and a pressure of 4.5 to 8.0 MPa to obtain a low-carbon alcohol mainly containing 1,2-propylene glycol, ethylene glycol, 1,2-butanediol and glycerol.

[0037] According to another preferred embodiment of the present invention, in step II, the reducing gas is hydrogen or a mixed gas composed of hydrogen and nitrogen in a volume ratio of 1:1 to 20.

[0038] The present invention will be described in more detail below.

[0039] The invention relates to a powdered Ni / La / SBA-15 catalyst.

[0040] The catalyst is composed of nickel oxide, lanthanum oxide and SBA-15 molecular sieve; wherein the content of nickel element is 10.0-25.0% based on the total weight of the catalyst, the content of lanthanum element is 3.0-10.0% based on the total weight of the catalyst, and the balance is the total content of oxygen element and SBA-15 molecular sieve; the nickel oxide is a face-centered cubic crystal with a grain size of less than 10nm; the lanthanum oxide is a hexagonal crystal with a grain size of less than 15nm; the specific surface area of ​​the catalyst is 350m 2 / g or above.

[0041] The SBA-15 molecular sieve has a two-dimensional hexagonal through-pore structure and has a P6mm space group. The SBA-15 molecular sieve used in the present invention is a product currently sold on the market, such as a product sold by Zhuoran Environmental Technology (Dalian) Co., Ltd. under the trade name SBA-15.

[0042] The nickel and lanthanum contents of the powdered Ni / La / SBA-15 catalyst of the present invention were determined by ICP-OES method, and it was determined that the nickel content was 5.0-15.0% and the lanthanum content was 2.5-9.0% based on the total weight of the catalyst.

[0043] The chemical structure of the powdered Ni / La / SBA-15 catalyst of the present invention was analyzed by conventional X-ray diffraction analysis method. The analysis results are listed in the attached Figure 1 The nickel oxide is a face-centered cubic crystal with a grain size of less than 10 nm, and the lanthanum oxide is a hexagonal crystal with a grain size of less than 15 nm.

[0044] The specific surface area of ​​the powdered Ni / La / SBA-15 catalyst of the present invention was measured by BET specific surface area test method, and its specific surface area was determined to be 350 m 2 / g or above.

[0045] The invention also relates to a method for preparing the powdered Ni / La / SBA-15 catalyst.

[0046] The preparation steps of the preparation method are as follows:

[0047] A. Preparation of mixed solution

[0048] 20.0-40.0 parts by weight of a soluble nickel salt, 2.0-10.0 parts by weight of a soluble lanthanum salt, 5.0-15.0 parts by weight of aqueous ammonia and 25.0-45.0 parts by weight of a fuel are stirred and mixed to obtain a mixed liquid;

[0049] According to the present invention, the main role of the soluble nickel salt in the method for preparing the powdered Ni / La / SBA-15 catalyst of the present invention is that it constitutes the catalytically active component in the preparation of lower alcohols by hydrogenation of sorbitol after reduction.

[0050] The soluble nickel salt used in the present invention is nickel nitrate, which is a product currently sold on the market, such as nickel nitrate sold by Sinopharm Chemical Reagent Co., Ltd. under the trade name nickel nitrate hexahydrate.

[0051] According to the present invention, the main function of the soluble lanthanum salt in the method for preparing the powdered Ni / La / SBA-15 catalyst of the present invention is to improve the dispersibility of nickel and the anti-carbon deposition performance of the catalyst.

[0052] The soluble lanthanum salt used in the present invention is lanthanum nitrate, which is a product currently sold on the market, such as the lanthanum nitrate sold by Sinopharm Chemical Reagent Co., Ltd. under the trade name lanthanum nitrate.

[0053] According to the present invention, the main function of the fuel in the method for preparing the powdered Ni / La / SBA-15 catalyst of the present invention is to increase the specific surface area of ​​the catalyst, reduce the nickel grain size, and improve the dispersion of nickel through the combustion expansion and heat release of the fuel.

[0054] The fuel used in the present invention is one or more organic fuels selected from glycine, ethylene glycol or citric acid, which are products currently sold on the market, such as glycine sold by Shanghai McLean Biochemical Technology Co., Ltd. under the trade name of glycine, and ethylene glycol sold by Shanghai McLean Biochemical Technology Co., Ltd. under the trade name of ethylene glycol.

[0055] According to the present invention, the main role of ammonia water in the method for preparing the powdered Ni / La / SBA-15 catalyst of the present invention is that it combines with nitrate ions in nickel and lanthanum metal salts to form ammonium nitrate. The decomposition of ammonium nitrate in the subsequent combustion and roasting steps can provide a large amount of heat and oxygen, which is conducive to obtaining the powdered Ni / La / SBA-15 catalyst.

[0056] The concentration of ammonia water used in the present invention is 25-28% by volume.

[0057] In this step, when the amounts of the soluble lanthanum salt, ammonia water and fuel are within the above ranges, if the amount of the soluble nickel salt is less than 20.0 parts by weight, the catalytic activity of the prepared catalyst is low; if the amount of the soluble nickel salt is more than 40.0 parts by weight, nickel loss and agglomeration are easily caused when preparing low-carbon alcohols by hydrogenation of sorbitol; therefore, it is reasonable to use 20.0 to 40.0 parts by weight of the soluble nickel salt, preferably 25.0 to 35.0 parts by weight, and more preferably 28.0 to 32.0 parts by weight;

[0058] When the amounts of soluble nickel salt, ammonia water and fuel are within the above ranges, if the amount of soluble lanthanum salt is less than 2.0 parts by weight, it cannot improve the nickel dispersibility and the anti-carbon deposition performance of the catalyst; if the amount of soluble lanthanum salt is more than 10.0 parts by weight, the proportion of lanthanum oxide in the catalyst is too large, and too many impurities are easily generated during the hydrogenolysis of sorbitol; therefore, the amount of soluble lanthanum salt is 2.0 to 10.0 parts by weight, preferably 4.0 to 8.0 parts by weight, and more preferably 5.0 to 7.0 parts by weight;

[0059] When the amount of soluble nickel salt, soluble lanthanum salt and fuel is within the above range, if the amount of ammonia water is less than 5.0 parts by weight, sufficient amount of ammonium nitrate cannot be generated; if the amount of ammonia water is more than 15.0 parts by weight, metal ions will form precipitates, affecting the dispersion of metal ions; therefore, the amount of ammonia water is 5.0 to 15.0 parts by weight, preferably 7.0 to 12.0 parts by weight, and more preferably 8.0 to 10.0 parts by weight;

[0060] When the amounts of soluble nickel salt, soluble lanthanum salt and ammonia water are within the range, if the amount of fuel is less than 25.0 parts by weight, a sufficient combustion reaction cannot be carried out; if the amount of fuel is more than 45.0 parts by weight, there is no obvious improvement on the catalyst performance and fuel waste is caused, which is uneconomical; therefore, a fuel amount of 25.0 to 45.0 parts by weight is desirable, preferably 28.0 to 42.0 parts by weight, and more preferably 32.0 to 40.0 parts by weight.

[0061] B. Mixing and drying

[0062] According to the volume ratio of the mixed liquid to the carrier of 1:0.8-1.2, the mixed liquid obtained in step A is added to the SBA-15 molecular sieve carrier, stirred and mixed evenly, and then allowed to stand at room temperature for 1-4 hours to allow the mixed liquid to be fully impregnated into the carrier, and then dried in an oven at a temperature of 80-110° C. for 12-16 hours to obtain a solid powder with a water content of less than 2.0% by weight;

[0063] The physical properties of the SBA-15 molecular sieve used in the present invention were measured by conventional X-ray diffraction analysis and BET specific surface area test method, respectively, and it was determined that its crystal form is hexagonal and its specific surface area is 400-1000m 2 / g, its total pore volume is 1.2-2.5ml / g, its average pore size is 5-15nm, and its particle size is 6250-12500 mesh. Experimental studies have shown that it is not advisable for the physical properties of SBA-15 molecular sieve to exceed the above range, because its specific surface area exceeding the above range will make the catalyst activity too low or too high, its total pore volume exceeding the above range will affect the service life of the catalyst, its average pore size exceeding the above range will affect the diffusion of the reactants, and its particle size exceeding the above range will affect the product yield due to its intra-particle diffusion.

[0064] The SBA-15 molecular sieve used in the present invention is a product currently sold on the market, such as the product sold by Zhuoran Environmental Protection Technology (Dalian) Co., Ltd. under the trade name SBA-15 and the product sold by Xi'an Ruixi Biotechnology Co., Ltd. under the trade name SBA-15.

[0065] The SBA-15 molecular sieve carrier used in the present invention has a low water absorption rate, and the mixed solution obtained in step A can be stirred and mixed to fully impregnate the SBA-15 molecular sieve carrier.

[0066] The main purpose of allowing the SBA-15 molecular sieve carrier and the mixed solution to stand for 1 to 4 hours at room temperature after stirring and mixing is to allow the carrier to fully adsorb metal ions. If the standing time is shorter than 1 hour, the SBA-15 molecular sieve carrier cannot fully adsorb metal ions; if the standing time is longer than 4 hours, the effect of adsorbing metal ions will not be significantly improved by extending the time; therefore, it is reasonable for the standing time to be 1 to 4 hours, preferably 1.5 to 3.5 hours, and more preferably 2.0 to 3.0 hours.

[0067] The SBA-15 molecular sieve carrier fully impregnated with the mixed solution is dried in an oven at a temperature of 80 to 110° C. for 12 to 16 hours to obtain a solid powder with a water content of less than 2.0% by weight.

[0068] In the present invention, when the impregnated SBA-15 molecular sieve carrier is dried in an oven, when the drying time is 12.0 to 16.0 hours, if the drying temperature is lower than 80°C, the drying effect is poor; if the drying temperature is higher than 110°C, the catalyst structure may be damaged; therefore, a drying temperature of 80 to 110°C is appropriate, preferably 85 to 104°C, and more preferably 90 to 98°C. When the drying temperature is 80 to 110°C, if the drying time is shorter than 12.0 hours, it cannot be fully dried; if the drying time is longer than 16.0 hours, the time cost is increased; therefore, a drying time of 12.0 to 16.0 hours is appropriate, preferably 12.6 to 15.4 hours, and more preferably 12.0 to 14.8 hours;

[0069] C. Combustion and roasting

[0070] The solid powder obtained in step B is ignited in a muffle furnace at a temperature of 300-350° C. for 0.5-1.0 h, then heated to 500-600° C. at a heating rate of 2-4° C. / min, and calcined at this temperature for 2-5 h to obtain the powdered Ni / La / SBA-15 catalyst.

[0071] In this step, the solid powder obtained in step B is burned in a muffle furnace to increase the specific surface area of ​​the catalyst, reduce the nickel grain size and improve the nickel dispersion; the combustion product is then roasted to enhance the bonding between the metal and the carrier;

[0072] When the solid powder obtained in step B is ignited in a muffle furnace, when the ignition time is 0.5 to 1.0 h, if the ignition temperature is lower than 300° C., the fuel is not easy to ignite; if the ignition temperature is higher than 350° C., the catalyst structure is easily destroyed; therefore, an ignition temperature of 300 to 350° C. is desirable, preferably 310 to 340° C., and more preferably 318 to 332° C. When the ignition temperature is 300 to 350° C., if the ignition time is shorter than 0.5 h, the fuel cannot be fully burned; if the ignition time is longer than 1.0 h, unnecessary energy consumption is increased; therefore, an ignition time of 0.5 to 1.0 h is appropriate, preferably 0.6 to 0.9 h, and more preferably 0.6 to 0.8 h.

[0073] After the muffle furnace is heated to 500-600° C. at a heating rate of 2-4° C. / min, the ignition product is calcined at this temperature for 2-5 hours to obtain the powdered Ni / La / SBA-15 catalyst.

[0074] When the calcination time is 2 to 5 hours, if the calcination temperature is lower than 500°C, the metal and the carrier are not firmly bonded; if the calcination temperature is higher than 600°C, the catalytic activity will be reduced; therefore, the calcination temperature is 500 to 600°C, preferably 520 to 580°C, and more preferably 540 to 560°C. When the calcination temperature is 500 to 600°C, if the calcination time is shorter than 2 hours, the metal and the carrier are not firmly bonded; if the calcination time is longer than 5 hours, the catalytic activity will be reduced; therefore, the calcination time is 2 to 5 hours, preferably 2.4 to 4.6 hours, and more preferably 2.8 to 4.2 hours.

[0075] The obtained powdered Ni / La / SBA-15 catalyst was subjected to chemical structure analysis, and the analysis results are as described above and will not be repeated here.

[0076] The obtained powdered Ni / La / SBA-15 catalyst was subjected to TEM-MAPPING (image analysis), and the analysis results are listed in the attached Figure 2 The quantitative results show that the nickel content on the catalyst surface reaches 25.0-70.0% at a resolution of 100 nm.

[0077] The present invention also relates to the use of the powdered Ni / La / SBA-15 catalyst or the powdered Ni / La / SBA-15 catalyst prepared by the preparation method in preparing low-carbon alcohols by hydrogenating sorbitol.

[0078] According to the present invention, the preparation steps of preparing low-carbon alcohols by hydrogenation of sorbitol are as follows:

[0079] I. Forming and filling

[0080] Using a tablet press, the powdered Ni / La / SBA-15 catalyst and powdered calcium hydroxide are respectively pressed into catalyst sheets and calcium hydroxide sheets with a diameter of 3 to 6 mm and a thickness of 2 to 5 mm, and then the catalyst sheets and calcium hydroxide sheets are mixed and filled into a fixed bed reactor at a weight ratio of 1:0.5 to 1.5 to form a catalyst bed;

[0081] In the present invention, the role of calcium hydroxide in preparing low-carbon alcohols by hydrogenation of sorbitol is to provide a base promoter for the hydrogenolysis reaction of sorbitol.

[0082] The weight ratio of the catalyst sheet to the calcium hydroxide sheet is 1:0.5-1.5. If the weight ratio of the catalyst sheet to the calcium hydroxide sheet is greater than 1:0.5, sufficient base promoters cannot be provided; if the weight ratio of the catalyst sheet to the calcium hydroxide sheet is less than 1:1.5, the catalytic activity is insufficient; therefore, the weight ratio of the catalyst sheet to the calcium hydroxide sheet is 1:0.5-1.5, preferably 1:0.7-1.3, and more preferably 1:0.8-1.2;

[0083] In the present invention, the catalyst bed composed of catalyst sheets and calcium hydroxide sheets is a cylindrical bed with a ratio of bed diameter to bed height of 1:70-120.

[0084] The fixed bed reactor used in the present invention is a device well known to engineers and technicians in the field, and is a fixed bed reactor widely sold in the market.

[0085] The tablet press used in the present invention is a tablet press commonly used in the art and widely sold in the current market;

[0086] II. Catalyst Activation

[0087] Allowing reducing gas to pass through the catalyst bed at a flow rate of 150 to 450 catalyst bed volumes per hour, while heating the catalyst bed to a temperature of 450 to 550° C. at a heating rate of 1.0 to 4.0° C. per minute, and activating the Ni / La / SBA-15 catalyst at this temperature for 2 to 5 hours;

[0088] In the present invention, the reducing gas is understood to be hydrogen or a mixed gas consisting of hydrogen and nitrogen in a volume ratio of 1:1 to 20.

[0089] In the catalyst activation, when the heating rate, activation temperature and activation time are within the range, if the reducing gas flow rate is less than 150 catalyst bed volumes / hour, the reduction is insufficient; if the reducing gas flow rate is greater than 450 catalyst bed volumes / hour, the reducing gas is wasted; therefore, a reducing gas flow rate of 150 to 450 catalyst bed volumes / hour is reasonable, preferably 180 to 420 catalyst bed volumes / hour, and more preferably 220 to 380 catalyst bed volumes / hour;

[0090] When the reducing gas flow rate, activation temperature and activation time are within the range, if the heating rate is lower than 1.0°C / min, unnecessary energy consumption will be increased; if the heating rate is higher than 4.0°C / min, the catalyst structure will be easily damaged; therefore, a heating rate of 1.0 to 4.0°C / min is appropriate, preferably 1.6 to 3.4°C / min, and more preferably 2.0 to 3.0°C / min;

[0091] When the reducing gas flow rate, heating rate and activation time are within the range, if the activation temperature is lower than 450°C, the catalyst cannot be fully reduced; if the activation temperature is higher than 550°C, the catalyst activity is reduced; therefore, the activation temperature is suitable to be 450-550°C, preferably 480-530°C, and more preferably 490-520°C;

[0092] When the reducing gas flow rate, heating rate and activation temperature are within the described range, if the activation time is shorter than 2 hours, the reduction is insufficient; if the activation time is longer than 5 hours, unnecessary energy consumption is increased; therefore, an activation time of 2 to 5 hours is appropriate, preferably 2.6 to 4.4 hours, and more preferably 2.8 to 4.0 hours.

[0093] Preferably, the reducing gas flow rate, heating rate, activation temperature and activation time are 180-420 catalyst bed volumes / hour, 1.6-3.4°C / min, 480-530°C and 2.6-4.4h respectively;

[0094] More preferably, the reducing gas flow rate, heating rate, activation temperature and activation time are 220-380 catalyst bed volumes / hour, 2.0-3.0°C / min, 490-520°C and 2.8-4.0h, respectively.

[0095] III. Hydrogenolysis

[0096] A mixed solution consisting of 10-50% sorbitol, 15-45% water and 30-60% methanol by weight is pumped into a fixed bed reactor through a pipeline. At the same time, high-pressure hydrogen is also transported into the fixed bed reactor through a pipeline. When the molar ratio of hydrogen to sorbitol is 10-30:1 and the feed volume space velocity is 0.5-2.5h -1 , reacting at a temperature of 190 to 240° C. and a pressure of 4.5 to 8.0 MPa to obtain a low-carbon alcohol mainly containing 1,2-propylene glycol, ethylene glycol, 1,2-butanediol and glycerol as a reaction product.

[0097] The hydrogenolysis reaction mechanism is as follows:

[0098]

[0099] In a mixed solution composed of sorbitol, water and methanol, when the amounts of methanol and water are within the above range, if the amount of sorbitol is less than 10%, the efficiency of the hydrogenolysis reaction is affected; if the amount of sorbitol is more than 50%, carbon deposition is likely to occur and more impurities are generated; therefore, it is reasonable to use sorbitol in an amount of 10 to 50%, preferably 18 to 42%, and more preferably 24 to 36%;

[0100] When the amount of sorbitol and methanol is within the above range, if the amount of water is less than 15%, sorbitol is difficult to dissolve completely; if the amount of water is more than 45%, the hydrothermal reaction is likely to damage the catalyst; therefore, the amount of water is appropriately 15-45%, preferably 18-40%, and more preferably 24-32%;

[0101] When the amount of sorbitol and water is within the range, if the amount of methanol is less than 30%, it is difficult to reduce the damage of water to the catalyst; if the amount of methanol is higher than 60%, it will cause methanol waste and increase production costs; therefore, it is desirable that the amount of methanol is 30-60%, preferably 38-52%, and more preferably 42-48%;

[0102] Sorbitol, methanol and hydrogen in a hydrogen to sorbitol molar ratio of 10 to 30:1, feed volume space velocity of 0.5 to 2.5 h -1 , reacting at a temperature of 190 to 240° C. and a pressure of 4.5 to 8.0 MPa to obtain a low-carbon alcohol mainly containing 1,2-propylene glycol, ethylene glycol, 1,2-butanediol and glycerol as a reaction product.

[0103] In the present invention, when the feed volume space velocity, temperature and pressure are within the range, if the molar ratio of hydrogen to sorbitol is lower than 10:1, the reaction activity is low; if the molar ratio of hydrogen to sorbitol is higher than 30:1, hydrogen is wasted; therefore, the molar ratio of hydrogen to sorbitol is appropriately 10 to 30:1, preferably 14 to 26:1, and more preferably 16 to 22:1;

[0104] When the molar ratio of hydrogen to sorbitol, temperature and pressure are within the ranges described above, if the feed volume space velocity is less than 0.5 h -1 , the output efficiency is too low; if the feed volume space velocity is higher than 2.5h -1 , the conversion rate of sorbitol is low; therefore, the feed volume space velocity is 0.5~2.5h -1 is suitable, preferably 0.8 to 2.1 h -1 , more preferably 1.2 to 1.8 hours -1 ;

[0105] When the molar ratio of hydrogen to sorbitol, the feed volume space velocity and the pressure are within the range, if the temperature is lower than 190°C, the reaction is difficult to occur; if the temperature is higher than 240°C, there are many side reactions, which affect the separation and purification of the product and the product yield; therefore, the temperature is appropriately 190 to 240°C, preferably 200 to 230°C, and more preferably 210 to 220°C;

[0106] When the molar ratio of hydrogen to sorbitol, the feed volume space velocity and the temperature are within the ranges, if the pressure is lower than 4.5 MPa, the reaction activity is affected and the yield is not high; if the pressure is higher than 8.0 MPa, there are many side reactions, and many impurities are easily generated, which affects the separation and purification of the product; therefore, a pressure of 4.5 to 8.0 MPa is suitable, preferably 4.8 to 7.5 MPa, and more preferably 5.2 to 7.0 MPa.

[0107] The hydrogenolysis products were analyzed by HPLC external standard method. The results are listed in the attached Figure 3 Attached Figure 3 The high performance liquid chromatography shows that the hydrogenolysis reaction products are mainly 1,2-propylene glycol, ethylene glycol, 1,2-butanediol and glycerol low-carbon alcohols, and their weight ratio is 1:0.4~0.6:0.1~0.2:0.3~0.6:.

[0108] According to the following formula, in the process of preparing low-carbon alcohols by hydrogenolysis of sorbitol, the conversion rate of sorbitol is above 96%.

[0109] Conversion rate % = amount of converted sorbitol / total amount of sorbitol in raw materials × 100%

[0110] According to the following formula, in the process of preparing low-carbon alcohols by hydrogenolysis of sorbitol, the total yield of low-carbon alcohols is more than 75%.

[0111] Total yield % = total amount of low-carbon alcohols in the product / theoretical amount of low-carbon alcohols × 100%

[0112] The catalyst life test of the present invention was carried out according to the standard of continuous reaction until the catalyst activity and selectivity decreased significantly. The results showed that the powdered Ni / La / SBA-15 catalyst of the present invention was still maintained at a specific surface area of ​​280 m2 in the experiment of preparing low-carbon alcohols by hydrogenolysis of sorbitol after 500 h of operation. 2 / g or above, indicating that it still has relatively high activity.

[0113] The conventional ICP analysis method is used to determine that the nickel loss is less than 0.5%. The conventional carbon-sulfur analyzer is used to determine that its carbon content is less than 0.5%. There is no obvious carbon deposition phenomenon, and it has high stability.

[0114] The powdered Ni / La / SBA-15 catalyst of the present invention has the following characteristics:

[0115] The present invention uses La 2 O 3 The dispersibility and anti-carbon deposition performance of the metal nickel surface are enhanced, the catalyst activity is enhanced by a combustion method, and methanol is added to the sorbitol reaction raw materials to reduce the damage of water to the catalyst, so that the catalyst exhibits high activity and high stability in the sorbitol hydrogenolysis reaction.

[0116] Beneficial Effects

[0117] The beneficial effects of the present invention are as follows: in the catalyst preparation method, the present invention enhances the catalyst activity by using fuel, and then enhances the surface dispersibility and anti-carbon deposition performance of metal nickel by adding lanthanum oxide. In addition, mixing calcium hydroxide with the catalyst to form a catalyst bed can greatly enhance the reaction activity, while reducing the production cost, thereby facilitating industrial wide application. The powdered Ni / La / SBA-15 catalyst of the present invention is applied to a method for preparing low-carbon alcohols by hydrogenating sorbitol, exhibiting good catalytic activity, a sorbitol conversion rate of greater than 96%, a low-carbon alcohol total yield of greater than 75%, and no significant decrease in activity and selectivity of the catalyst after running for 500 hours in a fixed bed reactor, and has good industrial application prospects. BRIEF DESCRIPTION OF THE DRAWINGS

[0118] Figure 1 This is an X-ray diffraction analysis diagram of the powdered Ni / La / SBA-15 catalyst of the present invention;

[0119] Figure 2 This is a TEM-MAPPING analysis diagram of the powdered Ni / La / SBA-15 catalyst of the present invention;

[0120] In the figure: black dots - silicon; white dots - nickel; gray dots - lanthanum;

[0121] Figure 3 It is a high performance liquid chromatogram of the hydrogenolysis reaction product of the present invention. DETAILED DESCRIPTION

[0122] The present invention will be better understood through the following examples.

[0123] Example 1: Preparation of Ni / La / SBA-15 powder catalyst of the present invention

[0124] The implementation of this embodiment is as follows:

[0125] A. Preparation of mixed solution

[0126] 40.0 parts by weight of nickel nitrate, 10.0 parts by weight of lanthanum nitrate, 15.0 parts by weight of 25% by volume ammonia water and 45.0 parts by weight of fuel glycine are stirred and mixed to obtain a mixed solution;

[0127] B. Mixing and drying

[0128] According to the volume ratio of the mixed liquid to the carrier of 1:1.0, the mixed liquid obtained in step A was added to the SBA-15 molecular sieve carrier, stirred and mixed evenly, and then allowed to stand at room temperature for 3 hours to allow the mixed liquid to be fully impregnated into the carrier, and then dried in an oven at a temperature of 110°C for 12 hours to obtain a solid powder with a water content of 2.0% by weight; the SBA-15 molecular sieve is a hexagonal crystal with a specific surface area of ​​650-850m 2 / g, its total pore volume is 1.8-2.1 ml / g, its average pore diameter is 6-11 nm, and its particle size is 6250-12500 mesh;

[0129] C. Combustion and roasting

[0130] The solid powder obtained in step B was ignited in a muffle furnace at 300° C., and after 1.0 h, the temperature was increased to 534° C. at a heating rate of 3° C. / min, and calcined at this temperature for 4 h to obtain the powdered Ni / La / SBA-15 catalyst.

[0131] According to the method described in the specification of this application, the catalyst is composed of nickel oxide, lanthanum oxide and SBA-15 molecular sieve; wherein the content of nickel element is 20.0% based on the total weight of the catalyst, the content of lanthanum element is 8.0% based on the total weight of the catalyst, and the balance is the total content of oxygen element and SBA-15 molecular sieve; the nickel oxide is a face-centered cubic crystal with a grain size of 9.8nm; the lanthanum oxide is a hexagonal crystal with a grain size of 14.0nm; the specific surface area of ​​the catalyst is 362m2 / g.

[0132] Example 2: Preparation of Ni / La / SBA-15 powder catalyst of the present invention

[0133] The implementation of this embodiment is as follows:

[0134] A. Preparation of mixed solution

[0135] 30.0 parts by weight of nickel nitrate, 8.0 parts by weight of lanthanum nitrate, 10.0 parts by weight of 28% by volume ammonia water and 35.0 parts by weight of fuel ethylene glycol were stirred and mixed to obtain a mixture solution;

[0136] B. Mixing and drying

[0137] According to the volume ratio of the mixture solution to the carrier of 1:0.8, the mixture solution obtained in step A was added to the SBA-15 molecular sieve carrier, stirred and mixed evenly, and then allowed to stand at room temperature for 1 hour to allow the mixture solution to be fully impregnated into the carrier, and then dried in an oven at a temperature of 80°C for 16 hours to obtain a solid powder with a water content of 1.9% by weight; the SBA-15 molecular sieve is a hexagonal crystal with a specific surface area of ​​400-600m 2 / g, its total pore volume is 1.3-1.5 ml / g, its average pore diameter is 5-9 nm, and its particle size is 6250-12500 mesh;

[0138] C. Combustion and roasting

[0139] The solid powder obtained in step B was ignited in a muffle furnace at 316° C., and after 0.8 h, the temperature was increased to 500° C. at a heating rate of 2° C. / min, and calcined at this temperature for 5 h to obtain the powdered Ni / La / SBA-15 catalyst.

[0140] According to the method described in the specification of this application, the catalyst is composed of nickel oxide, lanthanum oxide and SBA-15 molecular sieve; wherein the content of nickel element is 25.0% based on the total weight of the catalyst, the content of lanthanum element is 10.0%, and the balance is the total content of oxygen element and SBA-15 molecular sieve; the nickel oxide is a face-centered cubic crystal with a grain size of 9.8nm; the lanthanum oxide is a hexagonal crystal with a grain size of 14.8nm; the specific surface area of ​​the catalyst is 351m 2 / g.

[0141] Example 3: Preparation of powdered Ni / La / SBA-15 catalyst of the present invention

[0142] The implementation of this embodiment is as follows:

[0143] A. Preparation of mixed solution

[0144] 20.0 parts by weight of nickel nitrate, 2.0 parts by weight of lanthanum nitrate, 12.0 parts by weight of 26% by volume of ammonia water and 25.0 parts by weight of fuel citric acid are stirred and mixed to obtain a mixed solution;

[0145] B. Mixing and drying

[0146] According to the volume ratio of the mixed liquid to the carrier of 1:1.2, the mixed liquid obtained in step A was added to the SBA-15 molecular sieve carrier, stirred and mixed evenly, and then allowed to stand at room temperature for 4 hours to allow the mixed liquid to be fully impregnated into the carrier, and then dried in an oven at a temperature of 90°C for 14 hours to obtain a solid powder with a water content of 1.8% by weight; the SBA-15 molecular sieve is a hexagonal crystal with a specific surface area of ​​750-950m 2 / g, its total pore volume is 2.0-2.2 ml / g, its average pore diameter is 7-12 nm, and its particle size is 6250-12500 mesh;

[0147] C. Combustion and roasting

[0148] The solid powder obtained in step B was ignited in a muffle furnace at a temperature of 332° C., and after 0.5 h, the temperature was increased to 600° C. at a heating rate of 4° C. / min, and calcined at this temperature for 2 h to obtain the powdered Ni / La / SBA-15 catalyst.

[0149] According to the method described in the specification of this application, the catalyst is composed of nickel oxide, lanthanum oxide and SBA-15 molecular sieve; wherein the content of nickel element is 13.0% based on the total weight of the catalyst, the content of lanthanum element is 3.0% based on the total weight of the catalyst, and the balance is the total content of oxygen element and SBA-15 molecular sieve; the nickel oxide is a face-centered cubic crystal with a grain size of 9.6nm; the lanthanum oxide is a hexagonal crystal with a grain size of 14.9nm; the specific surface area of ​​the catalyst is 354m 2 / g.

[0150] Example 4: Preparation of Ni / La / SBA-15 powder catalyst of the present invention

[0151] The implementation of this embodiment is as follows:

[0152] A. Preparation of mixed solution

[0153] 38.0 parts by weight of nickel nitrate, 6.0 parts by weight of lanthanum nitrate, 5.0 parts by weight of 27% by volume ammonia water and 40.0 parts by weight of composite fuel glycine and ethylene glycol (mass ratio 3:1) were stirred and mixed to obtain a mixed solution;

[0154] B. Mixing and drying

[0155] According to the volume ratio of the mixed liquid to the carrier of 1:1.1, the mixed liquid obtained in step A was added to the SBA-15 molecular sieve carrier, stirred and mixed evenly, and then allowed to stand at room temperature for 2 hours to allow the mixed liquid to be fully impregnated into the carrier, and then dried in an oven at a temperature of 100°C for 13 hours to obtain a solid powder with a water content of 1.9% by weight; the SBA-15 molecular sieve is a hexagonal crystal with a specific surface area of ​​800-1000m 2 / g, its total pore volume is 2.3-2.5 ml / g, its average pore diameter is 9-15 nm, and its particle size is 6250-12500 mesh;

[0156] C. Combustion and roasting

[0157] The solid powder obtained in step B was ignited in a muffle furnace at a temperature of 350° C., and after 0.6 h, the temperature was increased to 570° C. at a heating rate of 3° C. / min, and calcined at this temperature for 3 h to obtain the powdered Ni / La / SBA-15 catalyst.

[0158] According to the method described in the specification of this application, the catalyst is composed of nickel oxide, lanthanum oxide and SBA-15 molecular sieve; wherein the content of nickel element is 23.0% based on the total weight of the catalyst, the content of lanthanum element is 5.0% based on the total weight of the catalyst, and the balance is the total content of oxygen element and SBA-15 molecular sieve; the nickel oxide is a face-centered cubic crystal with a grain size of 9.9nm; the lanthanum oxide is a hexagonal crystal with a grain size of 14.4nm; the specific surface area of ​​the catalyst is 356m 2 / g.

[0159] Example 5: Preparation of low-carbon alcohols by hydrogenation of sorbitol

[0160] The implementation of this embodiment is as follows:

[0161] I. Forming and filling

[0162] The powdered Ni / La / SBA-15 catalyst and powdered calcium hydroxide prepared in Example 1 were respectively pressed into catalyst sheets and calcium hydroxide sheets with a diameter of 5 mm and a thickness of 4 mm using a tablet press, and then the catalyst sheets and calcium hydroxide sheets were mixed and loaded into a fixed bed reactor at a weight ratio of 1:1.2 to form a catalyst bed with a bed diameter to bed height ratio of 1:120;

[0163] II. Catalyst Activation

[0164] The reducing gas of hydrogen was passed through the catalyst bed at a flow rate of 250 catalyst bed volumes / hour, and at the same time, the catalyst bed was heated to a temperature of 550°C at a heating rate of 3.0°C / min, and the Ni / La / SBA-15 catalyst was activated at this temperature for 3 hours;

[0165] III. Hydrogenolysis

[0166] A mixed solution consisting of 25% sorbitol, 15% water and 60% methanol by weight was pumped into a fixed bed reactor through a pipeline. At the same time, high-pressure hydrogen was also transported into the fixed bed reactor through a pipeline. At a hydrogen to sorbitol molar ratio of 30:1 and a feed volume space velocity of 1.8 h -1 The reaction was carried out under the conditions of 206°C, 8.0 MPa and 1,2-propylene glycol, ethylene glycol, 1,2-butylene glycol and glycerol. The conversion rate of preparing low-carbon alcohols by hydrogenolysis of sorbitol was 96.6% and the total yield was 75.8% according to the method described in the specification of the present application.

[0167] Example 6: Preparation of low-carbon alcohols by hydrogenation of sorbitol

[0168] The implementation of this embodiment is as follows:

[0169] I. Forming and filling

[0170] The powdered Ni / La / SBA-15 catalyst and powdered calcium hydroxide prepared in Example 4 were respectively pressed into catalyst sheets and calcium hydroxide sheets with a diameter of 3 mm and a thickness of 2 mm using a tablet press, and then the catalyst sheets and calcium hydroxide sheets were mixed and loaded into a fixed bed reactor at a weight ratio of 1:1.5 to form a catalyst bed with a bed diameter to bed height ratio of 1:90;

[0171] II. Catalyst Activation

[0172] A reducing gas consisting of hydrogen and nitrogen in a volume ratio of 1:20 was passed through the catalyst bed at a flow rate of 150 catalyst bed volumes / hour, and at the same time, the catalyst bed was heated to a temperature of 450°C at a heating rate of 1.0°C / min, and the Ni / La / SBA-15 catalyst was activated at this temperature for 4 hours;

[0173] III. Hydrogenolysis

[0174] A mixed solution consisting of 10% sorbitol, 40% water and 50% methanol by weight was pumped into a fixed bed reactor through a pipeline. At the same time, high-pressure hydrogen was also transported into the fixed bed reactor through a pipeline. At a hydrogen to sorbitol molar ratio of 10:1 and a feed volume space velocity of 0.5 h -1The reaction was carried out under the conditions of a temperature of 190°C and a pressure of 4.5 MPa. According to the method described in the specification of the present application, the reaction products obtained were low-carbon alcohols of 1,2-propylene glycol, ethylene glycol, 1,2-butylene glycol and glycerol. According to the method described in the specification of the present application, the conversion rate of preparing low-carbon alcohols by hydrogenolysis of sorbitol was calculated to be 96.8%, and the total yield was 76.2%.

[0175] Example 7: Preparation of low-carbon alcohols by hydrogenation of sorbitol

[0176] The implementation of this embodiment is as follows:

[0177] I. Forming and filling

[0178] The powdered Ni / La / SBA-15 catalyst and powdered calcium hydroxide prepared in Example 2 were respectively pressed into catalyst sheets and calcium hydroxide sheets with a diameter of 4 mm and a thickness of 3 mm using a tablet press, and then the catalyst sheets and calcium hydroxide sheets were mixed and loaded into a fixed bed reactor at a weight ratio of 1:0.5 to form a catalyst bed with a bed diameter to bed height ratio of 1:70;

[0179] II. Catalyst Activation

[0180] A reducing gas consisting of hydrogen and nitrogen in a volume ratio of 1:1 was passed through the catalyst bed at a flow rate of 350 catalyst bed volumes / hour, and at the same time, the catalyst bed was heated to a temperature of 480°C at a heating rate of 2.0°C / min, and the Ni / La / SBA-15 catalyst was activated at this temperature for 5 hours;

[0181] III. Hydrogenolysis

[0182] A mixed solution consisting of 20% sorbitol, 45% water and 35% methanol by weight was pumped into a fixed bed reactor through a pipeline. At the same time, high-pressure hydrogen was also transported into the fixed bed reactor through a pipeline. At a hydrogen to sorbitol molar ratio of 16:1 and a feed volume space velocity of 1.2 h -1 The reaction was carried out under the conditions of 224°C temperature and 5.6MPa pressure. According to the method described in the specification of the present application, the reaction products obtained were low-carbon alcohols of 1,2-propylene glycol, ethylene glycol, 1,2-butylene glycol and glycerol. According to the method described in the specification of the present application, the conversion rate of preparing low-carbon alcohols by hydrogenolysis of sorbitol was 96.4%, and the total yield was 76.6%.

[0183] Example 8: Preparation of low-carbon alcohols by hydrogenation of sorbitol

[0184] The implementation of this embodiment is as follows:

[0185] I. Forming and filling

[0186] The powdered Ni / La / SBA-15 catalyst and powdered calcium hydroxide prepared in Example 3 were respectively pressed into catalyst sheets and calcium hydroxide sheets with a diameter of 6 mm and a thickness of 5 mm using a tablet press, and then the catalyst sheets and calcium hydroxide sheets were mixed and loaded into a fixed bed reactor at a weight ratio of 1:0.8 to form a catalyst bed with a bed diameter to bed height ratio of 1:100;

[0187] II. Catalyst Activation

[0188] Allow hydrogen or a reducing gas consisting of hydrogen and nitrogen in a volume ratio of 1:10 to pass through the catalyst bed at a flow rate of 450 catalyst bed volumes / hour, and at the same time, heat the catalyst bed to a temperature of 520°C at a heating rate of 4.0°C / min, and activate the Ni / La / SBA-15 catalyst at this temperature for 2 hours;

[0189] III. Hydrogenolysis

[0190] A mixed solution consisting of 50% sorbitol, 20% water and 30% methanol by weight was pumped into a fixed bed reactor through a pipeline. At the same time, high-pressure hydrogen was also transported into the fixed bed reactor through a pipeline. At a hydrogen to sorbitol molar ratio of 24:1 and a feed volume space velocity of 2.5 h -1 The reaction was carried out under the conditions of 240°C temperature and 6.8MPa pressure. According to the method described in the specification of the present application, the reaction products obtained were low-carbon alcohols of 1,2-propylene glycol, ethylene glycol, 1,2-butylene glycol and glycerol. According to the method described in the specification of the present application, the conversion rate of preparing low-carbon alcohols by hydrogenolysis of sorbitol was 96.0%, and the total yield was 75.0%.

[0191] Comparative Example 1: Preparation of Low-Carbon Alcohols by Hydrogenation of Sorbitol

[0192] The implementation of this embodiment is as follows:

[0193] The powdered Ni / La / SBA-15 catalyst was prepared in the same manner as in Example 1, except that lanthanum nitrate was not used; the powdered Ni / SBA-15 catalyst without lanthanum nitrate was used to prepare low-carbon alcohols in the same manner as in Example 5. The conversion rate of the comparative example for preparing low-carbon alcohols by hydrogenolysis of sorbitol was 80.6%, and the total yield was 60.2%. It can be seen that the conversion rate and total yield of the comparative example 1 are much lower than those of the comparative example 5, which indicates that the lanthanum element has a greater effect on improving the catalytic activity and affecting the release of the product.

[0194] Comparative Example 2: Preparation of Low-Carbon Alcohols by Hydrogenation of Sorbitol

[0195] The implementation of this embodiment is as follows:

[0196] The lower alcohols were prepared in the same manner as in Example 6, except that methanol was not used; the conversion rate of the lower alcohols prepared by hydrogenolysis of sorbitol in this comparative example was 70.5%, and the total yield was 56.3%. It can be seen that the conversion rate and total yield of Comparative Example 2 were much lower than those of Example 6, which indicates that methanol has a greater effect on reducing the damage of hydrothermal treatment to the catalyst.

[0197] Comparative Example 3: Preparation of Low-Carbon Alcohols by Hydrogenation of Sorbitol

[0198] The implementation of this embodiment is as follows:

[0199] The lower alcohols were prepared in the same manner as in Example 7, except that calcium hydroxide was not used; the conversion rate of the lower alcohols prepared by hydrogenolysis of sorbitol in this comparative example was 60.1%, and the total yield was 54.8%. It can be seen that the conversion rate and total yield of Comparative Example 3 are much lower than those of Example 6, which indicates that calcium hydroxide plays an important role in improving the reaction activity and affecting the product distribution.

Claims

1. A method for preparing a powdered Ni / La / SBA-15 catalyst, characterized in that The preparation steps of the preparation method are as follows: A. Preparation of mixed solution 20.0-40.0 parts by weight of a soluble nickel salt, 2.0-10.0 parts by weight of a soluble lanthanum salt, 5.0-15.0 parts by weight of aqueous ammonia and 25.0-45.0 parts by weight of a fuel are stirred and mixed to obtain a mixed liquid, wherein the fuel is one or more organic fuels selected from ethylene glycol or citric acid; B. Mixing and drying According to the volume ratio of the mixed liquid to the carrier of 1:0.8-1.2, the mixed liquid obtained in step A is added to the SBA-15 molecular sieve carrier, stirred and mixed evenly, and then allowed to stand at room temperature for 1-4 hours to allow the mixed liquid to be fully impregnated into the carrier, and then dried in an oven at a temperature of 80-110° C. for 12-16 hours to obtain a solid powder with a water content of less than 2.0% by weight; C. Combustion and roasting The solid powder obtained in step B is ignited in a muffle furnace at a temperature of 300-350° C. for 0.5-1.0 h, then heated to 500-600° C. at a heating rate of 2-4° C. / min, and calcined at this temperature for 2-5 h to obtain the powdered Ni / La / SBA-15 catalyst.

2. The preparation method according to claim 1, characterized in that In step A, the soluble nickel salt is nickel nitrate.

3. The preparation method according to claim 1, characterized in that In step A, the soluble lanthanum salt is lanthanum nitrate.

4. The preparation method according to claim 1, characterized in that In step A, the concentration of the aqueous ammonia is 25-28% by volume.

5. The preparation method according to claim 1, characterized in that In step B, the crystal form of the SBA-15 molecular sieve is hexagonal, and its specific surface area is 400 to 1000 m 2 / g, its total pore volume is 1.2-2.5 ml / g, its average pore diameter is 5-15 nm, and its particle size is 6250-12500 mesh.

6. Use of the powdered Ni / La / SBA-15 catalyst prepared according to the preparation method according to any one of claims 1 to 5 in the preparation of lower alcohols by hydrogenation of sorbitol.

7. The use according to claim 6, characterized in that The preparation steps of preparing low-carbon alcohols by hydrogenation of sorbitol are as follows: I. Forming and filling Using a tablet press, the powdered Ni / La / SBA-15 catalyst and powdered calcium hydroxide are respectively pressed into catalyst sheets and calcium hydroxide sheets with a diameter of 3 to 6 mm and a thickness of 2 to 5 mm, and then the catalyst sheets and calcium hydroxide sheets are mixed and filled into a fixed bed reactor at a weight ratio of 1:0.5 to 1.5 to form a catalyst bed; II. Catalyst Activation Allowing reducing gas to pass through the catalyst bed at a flow rate of 150 to 450 catalyst bed volumes per hour, while heating the catalyst bed to a temperature of 450 to 550° C. at a heating rate of 1.0 to 4.0° C. per minute, and activating the Ni / La / SBA-15 catalyst at this temperature for 2 to 5 hours; III. Hydrogenolysis A mixed solution consisting of 10-50% sorbitol, 15-45% water and 30-60% methanol by weight is pumped into a fixed bed reactor through a pipeline. At the same time, high-pressure hydrogen is also transported into the fixed bed reactor through a pipeline. When the molar ratio of hydrogen to sorbitol is 10-30:1 and the feed volume space velocity is 0.5-2.5h -1 , reacting at a temperature of 190 to 240° C. and a pressure of 4.5 to 8.0 MPa to obtain a low-carbon alcohol mainly containing 1,2-propylene glycol, ethylene glycol, 1,2-butanediol and glycerol.

8. The use according to claim 7, characterized in that In step II, the reducing gas is hydrogen or a mixed gas consisting of hydrogen and nitrogen in a volume ratio of 1:1 to 20.

Citation Information

Patent Citations

  • High carbon polyol hydrocracking catalyst and preparing process and application thereof

    CN101199930A

  • A ruthenium catalyst with a regular structure and its preparation method

    CN101850249B

  • Application of Cu base loaded catalyst in preparation of low carbon diols by selective hydrogenolysis of high carbon polyols

    CN102731259A

  • Nickel-based bi-metallic catalyst with SBA-15 serving as a carrier and preparation method and application of catalyst

    CN103041839A

Cited By

  • Method for preparing low-carbon polyol from glucose

    CN121226128A